Comparing paclitaxel-platinum with ifosfamide-platinum as the front-line chemotherapy for patients with advanced-stage uterine carcinosarcoma. Issue 2 (7th February 2022) - Su, Ming-Hsuan; Wu, Hua-Hsi; Huang, Hsin-Yi; Lee, Na-Rong; Chang, Wen-Hsun; Lin, Shih-Chieh; Chen, Yi-Jen; Wang, Peng-Hui
Abstract : Background: Uterine carcinosarcoma (UCS) is a rare but highly lethal disease. Adjuvant chemotherapy is highly recommended for advanced UCS. To date, the standard chemotherapy regimen is still uncertain, although two regimens as paclitaxel-platinum (PP) and ifosfamide-platinum (IP) regimens are most commonly used. The aims of the current study attempt to compare both regimens in the management of advanced UCS patients. Methods: We evaluated advanced UCS patients who were treated either with PP or with IP after primary cytoreductive surgery in single institute retrospectively. The clinical-pathological parameters, recurrence, and survival were recorded. Results: A total of 16 patients were analyzed. Twelve patients received adjuvant PP therapy, and the remaining four patients received IP therapy. The median follow-up time was 28 months, ranging from 3.8 months to 121 months. Disease-related death occurred in 10 patients (62.5%). The median progression-free survival was 4.9 months, ranging from 3.8 months to 36.5 months in IP, and 23.1 months, ranging from 9.3 months to 121 months in PP, with statistically significant difference ( p = 0.04). The median overall survival was 9.5 months (ranging from 3.8 months to 36.5 months) and 28.7 months (ranging from 10.3 months to 121 months) in IP and PP, respectively, without statistically significant difference ( p = 0.06). Presence of pelvic and para-aortic lymphadenopathy and deep myometrial invasion (>1/2) were associated with worse prognosis by univariate analysis. No prognostic factor could be identified using multivariate analysis model. Conclusion: In the current study, due to extremely little number of subjects enrolled, the advantage of using paclitaxel-platinum regimen in the management of advanced UCS was still unclear, although a certain trend of favoring was supposed. We are looking forward to seeing more studies to identify the approximate regimen in the management of this highly lethal disease.